CONTRIBUTIONS TO BIRDWATCHING TOURISM: ETHNO-ORNITHOLOGY FOR SUSTAINABILITY IN THE NORTHERN SERTÃO HILLS, JAGUARARI – BA (Interdisciplinary Studies Journal, 2024)
The historical relationship between birds and humans is crucial, involving cultural manifestations and subsistence. Brazil stands out as the third country in avian endemism, especially in the Caatinga, imposing a conservation responsibility. Bird watching emerges as a vital tool for sustainable development, particularly in the mountainous areas of northern Bahia, an essential ecological corridor for biodiversity. Despite being strategic for Birdwatching, the region requires specific knowledge of local birds, connecting biomes and offering potential for ecotourism. This study aims to assess the tourist potential of avifauna in the mountainous region of Jaguarari, northern Bahia, based on Ethnoornithology and Human Ecology in high-altitude environments. Two promising routes were identified, such as Catuni Hills and Morgados Hills, cataloging various species, including those threatened with extinction, such as Araponga and Jacu. These birds can become icons for conservation programs, contributing not only to environmental protection but also to the local economy and the valorization of communities. The study aims to promote social inclusion in sustainable management, highlighting the importance of birds in the region and combating habitat destruction due to complex developments in mountainous regions.
Keywords: Avifauna; Birdwatching; Ecotourism; Human Ecology; Hills of the Sertão